Penggunaan Aplikasi Game Wordwall Pada Mata Pelajaran Akidah Materi Iman Kepada Para Malaikat - Nurismaya Aliatunisa; Faridi Faridi (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
The purpose of this research is to develop interactive learning media using Wordwall applications in Akidah subjects, especially the material of faith in angels, which is motivated by learning that is still monotonous and less innovative, so that it has an impact on student motivation and understanding that is less than optimal. Qualitative research with a descriptive approach was conducted through observations, interviews, and literature studies to develop Wordwall learning media. The results showed that the use of Wordwall interactive learning media proved effective in increasing students' motivation and understanding of the material of faith in angels, and the Wordwall application is considered to be an alternative learning media that is interesting and innovative, especially in online learning. This research emphasises the importance of the teacher's role in using learning media that suits the needs and characteristics of students, as well as utilising technological developments to make learning more interesting.